Dos especies nuevas para la avifauna argentina - Giacomo, Alejandro G. (1995)
First records for Argentina of the Tawny-rumped Tyrannulet (Phyllomyias uropygialis) and the Slate-throated Redstart (Myioborus miniatus) in Baritu National Park, in northern province of Salta.